ChemInform Abstract: A Photo‐Reagent System of Benzimidazoline and Ru(bpy)3Cl2 to Promote Hexenyl Radical Cyclization and Dowd—Beckwith Ring‐Expansion of α‐Halomethyl‐Substituted Benzocyclic 1‐Alkanones. Issue 36 (9th September 2014) - Hasegawa, Eietsu; Tateyama, Minami; Hoshi, Tsuneaki; Ohta, Taku; Tayama, Eiji; Iwamoto, Hajime; Takizawa, Shin‐ya; Murata, Shigeru
Abstract A benzimidazoline ligand in combination with a Ru‐ or Ir‐complex promotes photoinduced electron‐transfer reactions of α‐halomethyl substituted substrates to form primary alkyl radicals via selective C‐halogen bond cleavage.